2019
DOI: 10.1088/1755-1315/323/1/012177
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Sustainable Development Goals in construction industry - a systemic consideration of synergies and trade-offs

Abstract: According to sustainability research the world has exceeded four out of seven planetary boundaries. The areas of climate change, biodiversity loss, nitrogen cycle and land use have left the so called safe operating space for humanity. The built environment is one of the major contributors to environmental impacts. Especially the embodied energy during the construction phase of the built environment and the energy demands during the use of buildings contribute to a high energy and resource consumption. In the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…This means that the construction industry sees itself playing a pivotal role in achieving this goal by inclusively making cities and human settlements safe, resilient and sustainable. This finding concurs with that reported in other studies [35,66,67].…”
Section: Sustainable Cities and Communities (Sdg 11)supporting
confidence: 94%
See 1 more Smart Citation
“…This means that the construction industry sees itself playing a pivotal role in achieving this goal by inclusively making cities and human settlements safe, resilient and sustainable. This finding concurs with that reported in other studies [35,66,67].…”
Section: Sustainable Cities and Communities (Sdg 11)supporting
confidence: 94%
“…This SDG was ranked as second (MS = 4.56, SD = 0.570), an indication of the construction industry's seriousness towards achieving it (see Tables 3 and 4). Other related studies have identified this SDG [35,66,67] as important, especially as the construction industry worldwide seek ways to reduce their impacts on the environment.…”
Section: Sustainable Cities and Communities (Sdg 11)mentioning
confidence: 99%
“…Systems science is broken down into systems theory, systems analysis and cybernetics [56]. The perspectives gained from systems theory and cybernetics contributes to various interdisciplinary approaches.…”
Section: System Theory Systems Analysis System Dynamics and Systems Modelingmentioning
confidence: 99%
“…The Agenda 2030 can provide a framework for policy instruments and measures for transforming the construction industry in the interest of a more sustainable and healthier built environment. As the SDGs are interrelated and there are systemic interactions among the SDGs in the construction industry [138,139], some SDGs and their targets refer to air pollution. The topic of health is addressed in SDG target 3.9. and is also reflected in the articles, e.g., through the sick building syndrome or the topic of well-being in buildings, in schools and offices among others, and in the research field of indoor air pollution and indoor air quality.…”
Section: Discussionmentioning
confidence: 99%